Perancangan Alat Monitoring Kadar Gas CO2 Di Udara Berbasis NodeMCU ESP 8266 - Al Kautsar, Hanggoro Aji (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Air is one of the essential components for the survival of living things, air is a mixture of gases found in layers that surround the earth.Later, We were surprised by the rumors of air pollution happening in Indonesia, Especially in jakarta and beberaqpa other major cities in Indonesia.Without good air will surely be fatal to the respiratory system of humans and other living things on the face of the earth.Carbon (CO and CO2) is one of the materials found in the air and on the ground as carbonate rock, The gas has had a terrible impact on humans and other living things.If a living thing is exposed to that gas in a long time can result in death caused by a lack of oxygen intake. For that, The author performs the design and manufacture of carbon gas levels monitoring tools (CO and CO2) based on NodeMCU ESP 8266.Where the tool works by monitoring CO and CO2 levels that can provide information about CO and CO2 levels that then data from the gas levels will be sent directly to the whatsapp app and also through the LCD display and there will also be a warning alarm from the buzzer.Based on the tests that have been performed, the tool works to maximize the ability to monitor the levels of co and co2 gas sent to the whatsapp app and also be able to provide information via lcd and alarms through the buzzer when the levels of co and co2 exceed the previous threshold when the gas levels have returned to normal then the alarm will cease to sound and become normal